Qualidade de vida e capacidade funcional: associação da escala de performance de Karnofsky e questionário EORTC QLQ-C30 como preditor de saúde global em pacientes com câncer - Rech, Cinthya Raquel Alba (2018)
Clinical management of cancer patients involves primarialy the recovering of their biological health. This process is accompained by a psycosocial context, since cancer patients undergoing treatment fight profound bad feelings as pain, suffering, mutilation, destruction and death. Therefore, it is necessary to profoundly understand this patient, especially regarding the caracteristics that contribute to the mainentance and improvement of their quality of life. In this context, few instruments have been associated to evaluate the quality of life of patients ongoing chemotherapy, as well as it is not clear which specific component of such instruments influence the global health status of such patients.In the present study, we evaluated the relationship between the functional capacity and quality of life of cancer patients submitted to chemotherapy in a public health hospital from Brazil. To reach this goal, we used the Karnofsky performance scale and the EORTC QLQ-30 questionnaire as predictors of global health in patients with cancer. A total of 101 patients were enrolled in the study, from June to December 2017. All data were categorized accordingly and analyzed in SPSS 22.0.0 software for possible association among parameters. Patients presented a mean age of 59,6±13 years, and were predominatly female. Breast cancer was the most common neoplasia (43.56%), and most of patients exhibited advanced disease (73%) and distant metastasis (66.33%) at diagnosis. The global health score evaluated by EORTC QLQ-30 was 67.5%, and about 63% of patients presented a Karnofsky status of 80%. The most positive influent factor on the functional capacity was the working function (R = 0.515, p<0.05). Further, emotional and social functions were strongly associated with the global health status of patients (R = 0,960, p<0,05). Our data showed that the Karnofsky performance scale is a great tool for evaluating the quality of life in cancer patients undergoing chemotherapy, which correlates positively with their global health scores and is affected by emotional and social functions of patients.